2017
DOI: 10.2217/fon-2017-0426
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of MAC30 in advanced gastric cancer patients receiving platinum-based chemotherapy

Abstract: MAC30 could play as a potential biomarker for prognosis of GC with platinum-based chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Numerous studies demonstrated that TMEM97 was ubiquitously expressed in a wide variety of normal human tissues and cancer. TMEM97 mRNA and/or proteins was significantly increased in breast, colon, gastric, esophageal, lung, ovarian cancer and prostate cancer [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], but decreased in meningiomas, pancreatic and renal cancer [ 27 , 37 ]. TMEM97 upregulation in certain tumors and downregulation in others suggests that this protein plays a distinct role in human malignancies.…”
Section: Biological Characteristics and Functions Of σ 2mentioning
confidence: 99%
“…Numerous studies demonstrated that TMEM97 was ubiquitously expressed in a wide variety of normal human tissues and cancer. TMEM97 mRNA and/or proteins was significantly increased in breast, colon, gastric, esophageal, lung, ovarian cancer and prostate cancer [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], but decreased in meningiomas, pancreatic and renal cancer [ 27 , 37 ]. TMEM97 upregulation in certain tumors and downregulation in others suggests that this protein plays a distinct role in human malignancies.…”
Section: Biological Characteristics and Functions Of σ 2mentioning
confidence: 99%
“…Although immunotherapy is in full swing now, chemotherapy is still the cornerstone in the first-line therapy of advanced gastric carcinoma. Except for several single proteins ( 31 , 32 ), there has been no assessable clinical biomarker with prognostic value on chemotherapy in advanced gastric carcinoma. In our study, using TMB as a novel biomarker we divided patients into two groups and presented different clinical outcomes when treated with first-line chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11,12 ] MAC30 has been shown to be dysregulated in multiple cancers and is related to cancer progression, metastasis, treatment tolerance, and prognosis. [ 13–19 ] The downregulation of MAC30 effectively represses proliferation and invasion in cancer cells by affecting multiple signaling pathways. [ 20–22 ] This suggests that MAC30 is a potential and attractive anticancer target, which may be used for the development of tumor therapies.…”
Section: Introductionmentioning
confidence: 99%